PEMBINAAN PEDALANGAN DI SANGGAR MARDI BUDAYADESA WONOREJO KECAMATAN GONDANGREJO KABUPATEN KARANGANYAR - Sukatno Sukatno (Abdi Seni, 2016)
Traditional performance art and musical biscuits purwa Wonorejo Village, District Gondangrejo, District still exist and are embodied in the studio Mardi Culture. Coaching aims to enhance the skills of puppetry art of puppetry for the students, but it also made coaching for musicians and campursari. The coaching is done by using the method of appreciation, discussions, and demonstrations. The results obtained, the activity increased musicians crowded, the participants not only fathers and adolescents, but selian it every afternoon between the hours of 15:00 to 17:00  are used for training the local elementary school children. While every Tuesday night used by adolescents to exercise Mix, for Wednesday night for training activities Karawitan and puppetry by fathers, while the Saturday night to practice the activities of the local PKK. Given these activities  are very entertained residents, other than that if citizens have always used the musical intent of the PKK as well asfathers. With the existence of these musicians, all members of the community both young and old gamelan music lovers can sing or sing songs Mix. The success gained from this activity the participants are performing outside of the area.Therefore, the results are very good can be used to cover their daily needs. This indicates that the particular skills in the musical culture results could lift the economy for family or could provide for the family everyday.Key words: wayang kulit purwa, Karawitan, campursari